Relationship of Nurse Caring Behaviour with Patient Satisfaction at the Emergency Department of Catholic Hospital of Budi Rahayu Blitar - Suprajitno Suprajitno; Yeni Kartika Sari; Elizabeth Niken Budi Anggraeni (STIKes Patria Husada Blitar, 2020)
One indicator of hospital services is patient satisfaction related to nurses caring behaviour. The caring behaviour of nurses who provide nursing services in the Emergency Department is expected to increase the satisfaction of nursing services. The purpose of this study was to study the relationship between nurses caring behaviour with patient satisfaction receiving nursing services at the Emergency Department of Catholic Hospital of Budi Rahayu Blitar. The research design was cross sectional. Sample sizes were 80 patients who received nursing services at the Emergency Department were selected by purposive sampling. The study variables were nurse caring behaviour and patient satisfaction. Data were collected using a questionnaire. Analysis using the Spearman rank test. The analysis results obtained p = 0.000 and r = 0.618, which means there is a strong positive relationship between nurses caring behaviour with patient satisfaction. Suggestion, nurses maintain and even increase caring behaviour, especially communication skills in the orientation phase.